(untitled) (MAUSAM, 1963)
Heights of tops of clouds above 10 km determined by the storm detecting radar at, Dum Dum airport during the premonsoon months (March-June) of 1961 have been verified on some occasions by means of post-flight reports from high-level flying aircrafts. Occasionally, the radar clouds have been found to penetrate the tropopause and lower stratosphere. Instanctes of such cases reported by radiometeorologists in other countries have also been mentioned.